Competitive analysis: thinking beyond stage one - McManus, John; Botten, Neil (2006)
Strategic planning requires give and take of ideas and information. No person sees the total picture at first; what to communicate and why, is ambiguous; mindsets of various individuals have to be adjusted. But this iterative process cannot continue indefinitely. There action can proceed. Competitive analysis focuses on understanding the environment the firm competes within by developing strategies which allows the firm to build up a sustainable advantage in that industry. This paper focuses on the analytical and structural framework for competitive analysis, including the formulation of mission, objectives and strategic decisions. We also discuss the strategic importance of resources and competencies within the firm. - Reproduced.
Keywords: Strategic planning